Transformative Service and Managerial Roles Influence on Publik Satisfaction: A Case Study of Payakumbuh Public Service Mall - Saputra, Boni; Lanin, Dasman; Gomes da cruz Fernandes, Benjamin (Universitas Riau Kepulauan, 2026)
Public satisfaction is an important indicator in government agencies' assessment of the success and effectiveness of public services. Satisfaction reflects the extent to which the government has succeeded in meeting the needs and expectations of citizens and can be the basis for the improvement and development of policies that are more in line with community needs. This study analyzes the effect of transformative services and managerial roles on community satisfaction at the Payakumbuh Public Service Mall. The study employed a quantitative research design with an associative approach, utilizing data collected from 220 participants selected through simple random sampling methodology. Structural Equation Modeling (SEM) analysis was conducted using AMOS software to examine the hypothesized causal relationships among the constructs. The results showed that transformative services and the role of managers have a positive and significant influence on community satisfaction. The findings emphasize the importance of implementing transformative services and active managerial roles in improving public satisfaction with public services. This research provides valuable insights for public service managers to optimize service quality and managerial roles in meeting community expectations.